The Protection of Property under the ECHR with Special Regard to Central Europe and Former Yugoslav Republics - Plavšić , Nataša; Petrov , Vladan (The ECHR at 70: The Central European Narrative, 2025)
Although the right to the protection of property was not initially part of the original text of the European Convention on Human Rights, after the adoption of Protocol 1, this right experienced growth in the case law of the European Court of Human Rights. Special influence on the development of the right to possession in the case law of the Strasbourg Court goes to the cases decided against Central European countries and ex-Yugoslav Republics. The paper covers basic concepts of importance for a better understanding of the right to possession/property under Article 1 of Protocol 1 to the European Convention on Human Rights, as well as the case law of the European Court of Human Rights. The paper analyzes the autonomous meaning of possession/property, interference with property rights and a fair balance test. Finally, the paper presents some important cases decided against Central European countries and ex-Yugoslav Republics. These cases, in the authors’ opinion, contributed considerably to the progress of the case law of the European Court of Human Rights. Keywords: European Convention on Human Rights, European Court of Human Rights, Central European countries, ex-Yugoslav Republics, property, possessions, legitimate expectation, interference, deprivation or confiscation of property, control of property, a fair balance test, proportionality